Avaliação in situ do efeito anticariogênico de diferentes materiais restauradores - Sousa, Rosane Pontes de (2008)
Tooth structure immediately adjacent to restorations is susceptible to secondary caries, which may be caused by imperfect adaptation of restorative materials and subsequent microorganism colonization. Therefore, in order to identify methods of preventing secondary caries and increasing clinical dental restoration durability, different restorative dental materials have been introduced and applied in dental clinics. Thus, this in situ study assessed the effects of different restorative materials on the microbiological composition of dental biofilm and evaluated their ability of protecting the adjacent enamel against acid attacks from bacterial activity. A double-blind, split-mouth design was performed in one phase of 14 days, during which, 20 volunteers wore intra-oral palatal devices with five human enamel slabs, which were extra-orally restored according to the manufacturer’s specifications, using one of the following materials: Filtek Z 250/Single Bond composite resin; Permite amalgam; Fuji II encapsulated resin-modified glass ionomer; Vitremer resin-modified glass ionomer and Ketac Molar conventional glass ionomer.. During the experimental period, all subjects used fluoride-containing dentifrice 3x/day and a 20% sucrose solution was dripped onto the slabs 8x/day in predetermined times. The biofilm formed on the slabs was analyzed to determine total and mutans streptococci as well as lactobacilli counts. Demineralization (delta S) was determined on enamel by cross-sectional microhardness at 20 and 70 -µm from the restoration margin. In order to verify the differences among the treatments, Kruskal-Wallis and ANOVA followed by Minimum Squares test were applied for cariogenic microbiota and delta S, respectivly. No statistically significant differences were found in the cariogenic microbiota grown on the slabs. At 20-µm distance, only Fuji II statistically differed from the other groups presenting the lowest demineralization. At 70-µm, Fuji II significantly inhibited demineralization when compared to Permite, Filtek-Z-250 and Ketac Molar. Concluding, in the background of fluoride dentifrice and under the cariogenic exposure condition of this study, only the encapsulated resin-modified glass ionomer material provided additional protection against secondary caries.